Alpha-Mangostin Ameliorates Bleomycin-Induced Pulmonary Fibrosis in Mice Partly Through Activating Adenosine 5′-Monophosphate-Activated Protein Kinase - Li, Ren-shi; Xu, Gong-hao; Cao, Juan; Liu, Bei; Xie, Hai-feng; Ishii, Yuji; Zhang, Chao-feng (Frontiers in Pharmacology, 2019)
Background: Pulmonary fibrosis (PF) is a devastating interstitial lung disease and characterized by an abnormal accumulation of extracellular matrix (ECM). Nintedanib (NDN) and pirfenidone are two approved therapies for PF, but their potential side-effects have been reported. Recently, the use of natural supplements for PF is attracting attention. Alpha-mangostin (α-MG) is an active xanthone-type compound isolated from the nutritious fruit mangosteen. Purpose: In the present study, the potential effect and underlying mechanism of α-MG were evaluated in bleomycin (BLM)-induced PF and activated primary lung fibroblasts (PLFs). Methods: Histopathological changes and collagen deposition were analyzed via hematoxylin-eosin staining and Masson staining, the expression of NOX4 involved in oxidative stress in lung tissues was analyzed by immunochemistry staining. The expressions of α-SMA, Col I, p-AMPK/AMPK, and NOX4 were detected by Western blot, Immunofluorescence or RT-PCR, and effects of α-MG on cell viability were detected using the MTT. Results: In vivo results demonstrated that α-MG treatment (10 mg/kg/day) significantly ameliorated BLM-induced deposition of ECM in lung tissues. Moreover, α-MG could inhibit protein expressions of α-SMA and Col I as well as its mRNA levels. In addition, α-MG also significantly inhibited TGF-β1/Smad2/3 pathway and regulated the protein expression of MMP-9 and TIMP-1 in lung tissues. In vitro results demonstrated that α-MG significantly increased p-AMPK/AMPK but reduced the protein expression level of α-SMA and Col I as well as NOX4 in activated PLFs. Further study demonstrated that these improvement effects were significantly blocked by Compound C. Conclusion: α-MG treatment significantly decreased oxidative stress in lungs partly by activating AMPK mediated signalling pathway in BLM-induced PF and activated PLFs and decreased the deposition of ECM. The present study provides pharmacological evidence to support therapeutic application of α-MG in the treatment of PF.